2021
DOI: 10.3389/fmolb.2021.659168
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Identifies DCBLD2 as a Diagnostic and Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma

Abstract: Background: Accumulating evidence shows that the elevated expression of DCBLD2 (discoidin, CUB and LCCL domain-containing protein 2) is associated with unfavorable prognosis of various cancers. However, the correlation of DCBLD2 expression value with the diagnosis and prognosis of pancreatic ductal adenocarcinoma (PDAC) has not yet been elucidated. Methods: Univariate Cox regression analysis was used to screen robust survival-related genes. Expression pattern of selected genes was investigated in PDAC tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Previous work demonstrated that the SEMA4B and DCBLD2 interaction is involved in the regulation of the motility of lung cancer cell lines [ 14 ]. In addition, a recent study using PDAC cohorts reported that DCBLD2 was associated with poor survival in PDAC [ 15 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that the SEMA4B and DCBLD2 interaction is involved in the regulation of the motility of lung cancer cell lines [ 14 ]. In addition, a recent study using PDAC cohorts reported that DCBLD2 was associated with poor survival in PDAC [ 15 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Parameswaran et al demonstrated that FAM83A overexpression promotes tumor progression through the MEK-ERK signaling pathway in PDAC (56). DCBLD2 and DSG were identified as unfavorable prognostic biomarkers in PDAC (57,58). Notably, it has been reported that FOXM1 is overexpressed in hypoxic cancer cells, which is mediated by HIF-1 (59) et al also demonstrated that FOXM1 impelled the Warburg effect and tumor progression in PDAC through transcriptional modulation of LDHA expression, indicating that FOXM1 is a HIF-1 target affecting PDAC metabolism and progression (60).…”
Section: Discussionmentioning
confidence: 99%
“…Parameswaran et al demonstrated that FAM83A overexpression promotes tumor progression through the MEK-ERK signaling pathway in PDAC ( 56 ). DCBLD2 and DSG were identified as unfavorable prognostic biomarkers in PDAC ( 57 , 58 ). Notably, it has been reported that FOXM1 is overexpressed in hypoxic cancer cells, which is mediated by HIF-1 ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reported literature has revealed that DCBLD2 influences the emergence and progression of multiple diseases, including cancer ( Kikuta et al, 2017 ; He et al, 2020 ; Alhamoudi et al, 2021 ; Coppo et al, 2021 ; Feng et al, 2021 ). Moreover, DCBLD2 has been found to interact with the receptor tyrosine kinases EGFR, VEGFR, PDGFR, and INSR ( Nie et al, 2013 ; Feng et al, 2014 ; Schmoker et al, 2019 ; Schmoker et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%